Cognitive Informatics and Soft Computing Proceeding of CISC 2017 - Mallick, Pradeep Kumar; Balas, Valentina Emilia; Bhoi, Akash Kumar; Zobaa, Ahmed F. (Advances in Intelligent Systems and Computing, 2019)
The book presents new approaches and methods for solving real-world problems. It offers, in particular, exploratory research that describes novel approaches in the fields of Cognitive Informatics, Cognitive Computing, Computational Intelligence, Advanced Computing, Hybrid Intelligent Models and Applications. New algorithms and methods in a variety of fields are also presented, together with solution-based approaches. The topics addressed include various theoretical aspects and applications of Computer Science, Artificial Intelligence, Cybernetics, Automation Control Theory and Software Engineering.